Heterophoria in multiple sclerosis patients: a proof of principle cross-sectional study - Graf, Jonas; Weise, Margit; Guthoff, Tanja; Balloff, Carolin; Gasis, Marcia; Link, Heike; Küchlin, Sebastian; Lagrèze, Wolf; Meuth, Sven G.; Aktas, Orhan; Albrecht, Philipp (Frontiers in Immunology, 2024)
Objectives -The pathophysiology of multiple sclerosis (MS) involves inflammatory neurodegeneration in the brainstem, cerebellum and retina. The clinical relevance of oculomotor involvement in MS, however, remains uncertain.Methods -In this cross-sectional study, we evaluated heterophoria as a (sub)clinical tool in 54 MS patients and 55 age-matched healthy controls (HCs). We quantified heterophoria in prism diopters for distance and near range with orthoptic examination.Our primary outcome was high degrees of horizontal heterophoria (HDHH) defined as measurements beyond ±2 standard deviations from the mean prism diopter of heterophoria of our HCs.Results -More than one third (37%, n=20/54) of MS patients but only 11% (n=6/55) of HCs classified as HDHH (distance: MS=9% [n=5/54] versus HC=6% [n=3/55]; near: MS=19% [n=10/54] versus HC=5% [n=3/55]). Our MS patients presented more combined vertical and horizontal deviations at near (MS 19% [n=10/54] versus for HC 7% [n=4/55]). We observed the combination of HDHH both at distance and at near testing in 9% (n=5/54) of MS patients but not at all in HCs (n=0/55).Discussion -Despite the high prevalence of heterophoria, HDHH may be an additional (sub)clinical tool of subclinical involvement in MS. Thus, orthoptic examination may be an additional tool to improve MS diagnostic procedures.Author study concept/design, acquisition/survey/analysis/interpretation of data, drafting of the display items, drafting and revision of the manuscript TG Heinrich-